Human – machine interface research for traffic effectivity and safety - Schmeidler, Karel (Univerzita Pardubice, 2010)
Human factors and cognitive engineering competencies exist in Europe but are scattered. For addressing this fragmentation of research capacities, HUMANIST gathers the most relevant European research institutes involved in Road Safety and Transport to contribute to the eSafety initiative and to improve road safety by promoting human centred design for IVIS and ADAS.
Keywords: human-machine interface; ITS; traffic safety; IVIS; ADAS